Safety and efficacy of switching from adalimumab to sarilumab in patients with rheumatoid arthritis in the ongoing MONARCH open-label extension. Issue 2 (18th October 2019) - Burmester, Gerd R; Strand, Vibeke; Rubbert-Roth, Andrea; Amital, Howard; Raskina, Tatiana; Gómez-Centeno, Antonio; Pena-Rossi, Claudia; Gervitz, Leon; Thangavelu, Karthinathan; St John, Gregory; Boklage, Susan; Genovese, Mark C
Abstract : Objective: Evaluate open-label sarilumab monotherapy in patients with rheumatoid arthritis switching from adalimumab monotherapy in MONARCH (NCT02332590 ); assess long-term safety and efficacy in patients continuing sarilumab during open-label extension (OLE). Methods: During the 48-week OLE, patients received sarilumab 200 mg subcutaneously once every 2 weeks. Safety (March 2017 cut-off) and efficacy, including patient-reported outcomes, were evaluated. Results: In the double-blind phase, patients receiving sarilumab or adalimumab monotherapy showed meaningful improvements in disease activity; sarilumab was superior to adalimumab for improving signs, symptoms and physical function. Overall, 320/369 patients completing the 24-week double-blind phase entered OLE (155 switched from adalimumab; 165 continued sarilumab). Sarilumab safety profile was consistent with previous reports. Treatment-emergent adverse events were similar between groups; no unexpected safety signals emerged in the first 10 weeks postswitch. Among switch patients, improvement in disease activity was evident at OLE week 12: 47.1%/34.8% had changes ≥1.2 in Disease Activity Score (28 joints) (DAS28)-erythrocyte sedimentation rate/DAS28-C-reactive protein. In switch patients achieving low disease activity (LDA: Clinical Disease Activity Index (CDAI) ≤10; Simplified Disease Activity Index (SDAI) ≤11) by OLE week 24, 70.7%/69.5% sustained CDAI/SDAI LDA at both OLE weeks 36 and 48. Proportions of switch patients achieving CDAI ≤2.8 and SDAI ≤3.3 by OLE week 24 increased through OLE week 48. Improvements postswitch approached continuation-group values, including scores ≥normative values. Conclusions: During this OLE, there were no unexpected safety issues in patients switching from adalimumab to sarilumab monotherapy, and disease activity improved in many patients. Patients continuing sarilumab reported safety consistent with prolonged use and had sustained benefit.